Blood and urine physiological values in farm-cultured Rana catesbeiana (Anura: Ranidae) in Argentina - Coppo, José A.; Mussart, Norma B; Fioranelli, Santiago A. (Revista de Biología Tropical, 2005)
A total of 302 samples of healthy farm-cultured Rana catesbeiana specimens (9-21 months-old, 50- 350 g liveweight, 50% each sex) from the north-east of Argentina, were analyzed through spectrophotometry, electrophoresis, densitometry, refractometry and microscopy in order to obtain blood and urine normal values. Confidence intervals (p<0.05) for PCV (28.6-31.6%), RBC (0.40-0.44 T/L), MCV (686-732 fL), hemoglobin (6.41-7.20 g/dL), MCH (151-164 pg), MCHC (22.6-24.0%), WBC (18.7-22.3 G/L), neutrophils (58.4-63.4%), lymphocytes (23.9-29.8%), monocytes (2.1-3.8%), eosinophils (4.6-7.0%), basophils (2.9-4.1%), bleeding time (289-393s), coagulation time (452-696s), prothrombin time (76-128s), urinary density (1.0061-1.0089 g/mL), urinary pH (6,38-6.96), fibrinogen (0.59-0.99 g/dL), total protein (4.19-4.49 g/dL), albumin (1.49-1.67 g/dL), alpha-1 globulin (0.20-0.24 g/dL), alpha-2 globulin (0.48-0.54 g/dL), beta globulin (0.68-0.77 g/dL), gamma globulin (1.28-1.42 g/dL), albumin/globulin ratio (0.50-0.58), creatinine (4.09-5.56 mg/L), urea (76.1-92.4 mg/L), uric acid (11.5-15.4 mg/L), triglycerides (0.34-0.52 g/L), total cholesterol (0.56-0.67 g/L), HDL-C (0.03-0.05 g/L), LDL-C (0.34-0.44 g/L), alpha lipoprotein (6.01-8.67%), beta lipoprotein (91.3-93.9%), glucose (0.45-0.54 g/L), Na (116-121 meq/L), K (3.42-3.81 meq/L), Cl (100-116 meq/L), Ca (7.98-8.61 mg/dL), P (8.31- 9.36 mg/dL), Mg (2.26-2.55 mg/dL), Fe (105-178 ug/dL), ALP (144-170 IU/L), ALT (10.0-14.8 IU/L), AST (42.8-53.4 IU/L), GGT (7.8-10.6 IU/L), LDH (99-135 IU/L), CHE (151-185 IU/L) and CPK (365-500 IU/L), were obtained. Some parameter ranges were similar to those obtained in amphibians, birds or mammals; others were very different. These parameters are useful to evaluate sanitary, metabolic and nutritional state on captive bullfrogs